2007
DOI: 10.1002/pssa.200674368
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Pd layer on the sensitivity of CHx/PS/Si as structure for H2 sensing

Abstract: In this work, a hydrogen sensor based on Palladium/hydrocarbons (CHx )/Porous silicon/Silicon structure has been studied in presence of hydrogen gas. Current–voltage characterizations show that the sensitivity of the sensor is improved by more than two orders of magnitude compared with the uncoated CHx /PS/Si device. In addition, a rapid response time of the sensor of about 10 s is measured. (© 2007 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…This is slightly different from the results obtained for PSi/CH x and PSi/CH x /Pd structures where the maximum sensitivity was observed at 30 [6] and 10 mV, respectively. [7] In the presence of cigarette smoke, a maximum sensitivity for the PSi/poly(3-hexylthiophene) structure was obtained at 10 mV (a in Fig. 5).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…This is slightly different from the results obtained for PSi/CH x and PSi/CH x /Pd structures where the maximum sensitivity was observed at 30 [6] and 10 mV, respectively. [7] In the presence of cigarette smoke, a maximum sensitivity for the PSi/poly(3-hexylthiophene) structure was obtained at 10 mV (a in Fig. 5).…”
Section: Resultsmentioning
confidence: 98%
“…[5,6] It was demonstrated that the detection of hydrogen was improved by depositing a thin layer of palladium on the organic coating (CH x ). [7] In the continuation of our work on the use of PSi for gas sensing and to improve the stability and conductivity of the sensor, we propose the covalent grafting of organic conductive species such as conducting polymers onto the PSi surface. The choice of conductive polymers is essential in this application.…”
Section: Introductionmentioning
confidence: 99%
“…In the H 2 pressure range, the palladium modified PS structure exhibits higher amplitude of (I) responses than that of the Pd/Si (Fig. 4) or CHx/PS/Si structures [1,12]. The difference between the hydrogen sensitivity of porous silicon with and without Pd can be explained by the model proposed by Rahimi et al [13].…”
Section: Resultsmentioning
confidence: 99%